'You Can't Always Get What You Want': The effects of winning and losing in a referendum on citizens' referendum support. (June 2020) - Brummel, Lars
Abstract: In Western democracies, many citizens support the use of referendums. However, as referendums create satisfying outcomes for citizens with majority views, they could generate ambivalent feelings among voters for the minority option. Little is known about the effects of winning or losing a referendum for citizens' referendum support. This article analyses multiple-wave survey data from five referendums in Bavaria (Germany), Finland and the Netherlands. The findings show that losers' referendum support decreases in nearly all cases, but there is very limited evidence for an increase of winners' referendum support. Nevertheless, the results clearly indicate a winner-loser gap, suggesting that referendums have relatively more positive effects for winners' than for losers' referendum support. As such, this article extends previous findings of the non-stability of referendum support. As the legitimacy of democratic institutions depends upon losers' consent, these findings have important implications for the democratic potential of referendums.